Quantitative analysis of lead in polysulfide-based impression material - Braga, Aparecida Silva; Braga, Sebastião Roberto Silva [UNESP]; Catirse, Alma Blásida Concepción Elizaur Benitez; Vaz, Luis Geraldo [UNESP]; Mollo Junior, Francisco De Assis [UNESP] (ABM, ABC, ABPol, 2007)
Permlastic® is a polysulfide-based impression material widely used by dentists in Brazil. It is composed of a base paste and a catalyzer containing lead dioxide. The high toxicity of lead to humans is ground for much concern, since it can attack various systems and organs. The present study involved a quantitative analysis of the concentration of lead in the material Permlastic®. The lead was determined by plasma-induced optical emission spectrometry (Varian model Vista). The percentages of lead found in the two analyzed lots were 38.1 and 40.8%. The lead concentrations in the material under study were high, but the product’s packaging contained no information about these concentrations.
Keywords: Permlastic®; impression materials; polysulfides; lead